2018
DOI: 10.1002/mmce.21574
|View full text |Cite
|
Sign up to set email alerts
|

A CNTFET universal mixed‐mode biquad active filter in subthreshold region

Abstract: This paper presents a new low‐voltage and low‐power mixed‐mode universal active filter, using only 12 carbon nanotube field effect transistors (CNTFETs) and 2 grounded capacitors to improve the noise performance of the proposed circuit. Due to the use of subthreshold transistors biased at ±0.2 V supply voltage, the power consumption of the proposed multi input‐single output (MISO) filter is only 850 nW at 19 MHz center frequency. On the other hand, relaxing from any matching components, the center frequency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Further, Table 3 shows that the CNTFET‐AGI is outperforming the CMOS‐AGI in terms of power dissipation, temperature insensitivity behavior, and Q factor with reduced die area of 0.16 μm 2. 41 Also, the proposed circuit is outperforming the conventional one in the in‐noise and out‐noises parameters also. This clearly shows that the proposed CNTFET‐AGI is more reliable and robust than the conventional CMOS‐AGI.…”
Section: Realization Of Agi Using the Proposed Cciismentioning
confidence: 86%
“…Further, Table 3 shows that the CNTFET‐AGI is outperforming the CMOS‐AGI in terms of power dissipation, temperature insensitivity behavior, and Q factor with reduced die area of 0.16 μm 2. 41 Also, the proposed circuit is outperforming the conventional one in the in‐noise and out‐noises parameters also. This clearly shows that the proposed CNTFET‐AGI is more reliable and robust than the conventional CMOS‐AGI.…”
Section: Realization Of Agi Using the Proposed Cciismentioning
confidence: 86%
“…Marani et al reported improvement in DC gain by 17%, 40% less power consumption, and a decrease in output resistance by 90% in comparison to CMOS OTA [7]. Low power mixed-mode active fi lter using 12 CNT and 2 capacitors was presented by Zanjani et al [14]. Jooq et al designed CNTFET based ring oscillators suitable for the internet of things (IoT) applications [17].…”
Section: Univerzalni Filtri In Oscilatorji Na Osnovi Napetostnega Tramentioning
confidence: 99%
“…Where, tight binging energy t is 3.0eV (also referred to as C-C bonding energy) and C-C bonding distance a cc of the nearest neighbor is 1.42A o . Whereas, equations for CNT diameter CNTFET threshold are given as [13]- [14]:…”
Section: Carbon Nanotube Field-effect Transistors Fundamentalsmentioning
confidence: 99%
“…Among these solutions, CNTFET is considered as a promising alternative for future extension of Moore's law due to its efficient electrostatic control, ballistic transport of charge carriers, large thermal conductivity, lesser parasitics, higher cutoff frequency, large drive current and low power dissipation to name a few [26][27][28]. Since introduction of CNTFET as an emerging device and better alternative of bulk semiconductor technology, limited work on CNTFET based circuit design has been carried out in analog filtering domain [10,18,26,27,29,30]. This work aims to realize new APF topologies with compact circuit structures for low voltage, low power and high frequency fully differential applications.…”
Section: Introductionmentioning
confidence: 99%